Life-cycle assessment of different building technologies for partion walls : contribution to future developments on interior partition concepts - Mateus, Ricardo (2011)
The growing necessity to save material and energy resources, together with a growing concern over the environmental issues, are impelling to solutions that present a minimal expression of the materials and products used. This is particularly relevant to the interior partition walls that have a high contribution to the environmental impact of buildings, although these elements are easily reducible. Another aspect is that a great portion of housing designs are not flexible in use and therefore they are not suitably adjustable to the permanent updating of life-styles and variations on the composition of the households. Although there are some lightweight building technologies, in most cases the construction practice in Portugal makes use of heavyweight and static partition walls. This problem reveals to be of particularly importance in the refurbishment phase of existing buildings, but also when it is necessary the rethink of the interior spaces in the operation phase. The aim of this paper is to analyse the environmental, functional and economical performances of a conceptual lightweight sandwich membrane partition wall and to compare it with two technologies: i) the heavyweight conventional partition wall (hollow brick wall); and ii) the lightweight reference gypsum panels wall (plasterboard wall). This paper will be focused in the advantages of the lightweight partition walls and may contribute for the development of new partition wall technologies. The comparative evaluation of these solutions will be based on a standard Life-cycle Assessment method. A lightweight interior partition walls is certainly a wiser option in many situations as it can be more flexible and even portable, in some cases, as well as having a lower environmental impact in a Life-cycle Assessment (LCA), as it will be demonstrated in this paper. The lower quantity of materials used in lightweight solutions allow a lower specific embodied energy and other more favourable environmental impact indicators. The reduction of material inputs to the minimum is a way to achieve higher eco-efficiency in a building and thus open the road to more efficient interior partition systems.